Synthesis and metal complexation of a new oxime derivative of 2-aminothiazole - Cukurovali, A; Tas, E; Ahmedzade, M (Marcel Dekker Inc, 1997)
2-anti-Glyoximatoamino-4-(o,p-tolyl)thiazole was synthesized as an analog of alkyl thiazoles. This compound was used as a complexing agent for Cu(II), Ni(II), and Co(II). The authenticity of the ligand and complexes was established by elemental analyses, infrared spectra, H-1 NMR, magnetic measurements and thermogravimetric analyses (TGA).
Keywords: Crystal-Structures; Cobalt(Ii); Ligands